Consulting Readings of Home Blood Pressure Monitoring With Doctor Increases the Effectiveness of Antihypertensive Therapy in Daily Clinical Practice - Chudek, Jerzy; Owczarek, Aleksander Jerzy; Olszanecka-Glinianowicz, Magdalena; Almgren-Rachtan, Agnieszka (Cardiology and Cardiovascular Medicine, 2019)
Background: The routine home blood pressure monitoring (HBPM) is strongly recommended for management of hypertension, however the evidence concerning the improvement of blood pressure (BP) control related to self-measurement of BP is weak. The aim of this study was to assess the efficacy of antihypertensive therapy in relation to the consulting of HBPM readings with physicians in daily clinical practice. Patients & methods: The survey was conducted by 627 physicians among 21,940 hypertensive patients, of whom 17,143 (8,972 women and 8,171 men; mean age of 63 ± 12 years) were receiving antihypertensive medication for at least 6 months. BP control was scored based on two office BP measurements (< 140/90 mmHg). Results: Among patients declaring performing HBPM (N = 14,524), 86.6% were consulting the readings with physicians. Patients consulting the readings had lower systolic (by 6.4 mmHg) and diastolic (by 3.4 mmHg) BP than those not consulting their HBPM results, and by 5.3 and 4.5 mmHg than those not measuring BP at home. Patients consulting the HBPM results were obtaining more frequently recommended BP control (54.2%). BP control was similar in patients performing but not consulting HBPH readings and not doing HBPM (35.8 and 35.7%, respectively). Conclusion: The benefits of home blood pressure monitoring are restricted to patients consulting the readings with physicians.